Quality Assurance in Teacher Education - Komorowska, Hanna (Glottodidactica, 2017)
Quality in general education has been defined through aims, key qualifications, organisational standards, didactic requirements, but also learning outcomes which depend on students’ proficiency in the language of schooling and their cognitive academic skills. New challenges bring about changes in responsibilities of schools and teachers and have a strong impact on approachesto quality assurance in teacher education, a complex process not devoid of controversies, the most important of which will be identified in the present text. Implications for the curricular content of pre- and in-service language teacher education will also be sought.